Self-repairing invisible car cover and preparation method thereof
By using a self-healing coating composed of fluoropolymer polyols, polyisocyanates, composite chain extenders and self-healing microcapsules in the invisible car clothing, the problem of the lack of self-healing ability in the face of slight scratches and wear is solved, and the rapid self-healing and long-life protection of the car clothing is achieved.
Patent Information
- Application Number
- CN202411727210.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-11-28
AI Technical Summary
The existing invisible car cover lacks effective self-repair capabilities in the face of slight scratches and wear, resulting in short service life and high maintenance costs.
The self-healing coating consisting of fluorine-containing polyols, polyisocyanates, composite chain extenders and self-healing microcapsules is used to realize the self-healing function of the car coat through synergistic action.
After the car coat is damaged, it can quickly achieve self-repair, extend the service life of the car paint, reduce maintenance costs, and maintain good aesthetics.
Smart Images

Figure BDA0005159484070000101 
Figure BDA0005159484070000111 
Figure HDA0005159484080000011
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of automobile material processing, and in particular to a self-repairing invisible car cover and a preparation method thereof. Background Art
[0002] As an effective tool to protect the car surface from scratches, corrosion and other damage, invisible car cover has been widely used in the car beauty and protection market. As consumers' demand for vehicle appearance protection continues to increase, the market demand for invisible car cover is also growing year by year.
[0003] Traditional invisible car covers are mainly composed of one or more layers of polymer materials, which protect the car paint by physical covering. They mainly include single-layer polymer materials and multi-layer composite materials. Single-layer polymer materials are usually made of polyurethane, polyvinyl chloride and other materials, which have certain flexibility and weather resistance, but their scratch resistance is weak and they are easily affected by environmental factors and age. Multi-layer composite materials improve the overall performance of the product by stacking material layers with different functions.
[0004] Although the invisible car cover in the existing technology can protect the car paint to a certain extent, it lacks effective self-repair ability when facing minor scratches and wear, resulting in a short service life and high maintenance cost, so it needs to be improved. Summary of the invention
[0005] In order to improve the self-repairing performance of invisible car cover, the present application provides a self-repairing invisible car cover and a preparation method thereof.
[0006] The present application provides a self-repairing invisible car cover and a preparation method thereof using the following technical solutions: In the first aspect, the present application provides a self-repairing invisible car cover, which adopts the following technical solution: A self-repairing invisible car cover comprises a protective film, a self-repairing coating, a transparent substrate, an adhesive layer and a release film which are arranged in sequence. The self-repairing coating is obtained by coating a self-repairing coating. The raw materials for preparing the self-repairing coating include the following components in parts by weight: 20-40 parts of fluorinated polyol Polyisocyanate 15-30 parts 5-10 parts of composite chain extender Self-repairing microcapsules 10-20 parts Initiator 1-3 parts 30-50 parts of solvent.
[0007] Fluorinated polyols reduce surface energy by introducing fluorine atoms, which can improve the weather resistance and chemical corrosion resistance of car covers and prevent stains from adhering. Polyisocyanates react with fluorinated polyols to form a polyurethane network structure, which provides good mechanical strength and stability for the coating and can improve the ability of the car cover to resist scratches. Composite chain extenders can effectively adjust the length and structure of the polyurethane chain, enhance the flexibility and tensile properties of the car cover, and prevent it from breaking when stretched or bent by external forces. Self-healing microcapsules are evenly dispersed in the coating. When scratches and other minor damages appear on the surface of the car cover, the microcapsules break and release repair substances to repair the damaged parts, thereby restoring the integrity and protective function of the car cover. Through the synergistic effect of various components, the self-healing invisible car cover can achieve rapid self-repair after being damaged, effectively reducing damage to the car paint during long-term use, and has a long service life and good aesthetics.
[0008] Preferably, the raw materials for preparing the fluorine-containing polyol include bio-based polyol and perfluorohexylpropylene oxide.
[0009] Perfluorohexylpropylene oxide introduces fluorine atoms, giving the material a special molecular structure, which allows the molecular chains to rearrange after being damaged by scratches, prompting the damaged molecular chains to adjust to their original state and enhancing the self-healing properties; the presence of fluorine improves the UV resistance of the car cover, can effectively absorb and scatter ultraviolet rays, and prevent ultraviolet rays from destroying the molecules in the material. At the same time, the fluorine-containing groups enhance the chemical stability of the material and improve weather resistance; the network structure formed by the polymerization of bio-based polyols and perfluorohexylpropylene oxide has good flexibility and cohesion, and the dense structure formed by the fluorine-containing polyols can enhance the overall hardness and toughness of the car cover, improve the tensile and puncture resistance of the car cover, effectively resist damage from external forces, and extend the service life of the car cover.
[0010] Preferably, the mass ratio of the bio-based polyol to perfluorohexylpropylene oxide is 1:(0.1-0.3).
[0011] The fluorinated polyol prepared according to the above mass ratio has good performance and can effectively improve the self-repairing performance, weather resistance, tensile strength and puncture resistance of the invisible car cover.
[0012] Preferably, the composite chain extender includes 4,4'-diaminodiphenyl disulfide and modified magnolol chain extender.
[0013] 4,4'-diaminodiphenyl disulfide can increase the length and cross-linking degree of the molecular chain, so that there are more interaction points between the molecular chains. Functional groups such as amino groups can form hydrogen bonds in the coating system. The phenolic hydroxyl groups in the modified magnolia phenol can also promote the more orderly movement and rearrangement of the molecular chains through hydrogen bonding, thereby repairing scratches and improving the self-healing performance of the invisible car cover. The modified magnolia phenol has good antioxidant properties and can resist the erosion of the car cover by environmental factors such as ultraviolet rays and oxygen in the air. The chemical bond structure in 4,4'-diaminodiphenyl disulfide is stable. The combined effect of the two can reduce the aging and degradation of the material caused by long-term exposure to the external environment, thereby improving the weather resistance of the car cover. The increase in cross-linking degree and intermolecular interaction enhances the overall strength of the invisible car cover, so that when the material is subjected to external force, the molecular chains can bear the force together and evenly disperse the stress, preventing the car cover from rupture due to excessive local force, better protecting the car paint, and improving the tensile strength and puncture resistance.
[0014] Preferably, the raw materials for preparing the modified magnolol chain extender include magnolol body, silane coupling agent and nano-silicon dioxide.
[0015] Nano-silica modified magnolia phenol, with silane coupling agent as a bridge, can effectively introduce uniformly dispersed nano-silica into the coating. Nano-silica can reinforce defects in the molecular chain, improve its strength, and provide physical space and restrictions for the movement of the molecular chain. When the car cover is damaged, it can prompt the car cover to adjust its position more orderly and rearrange to repair scratches. Nano-silica can enhance the car cover's ability to reflect and scatter ultraviolet rays, and reduce the damage of ultraviolet rays to the internal structure of the car cover. Magnolia phenol can enhance the antioxidant properties. The synergistic effect of the two can extend the service life of the car cover and improve its weather resistance. The modified magnolia phenol chain extender introduces nano-silica into the coating molecular chain. The combination of the two enables the car cover to effectively disperse stress, reduce the occurrence of cracks and punctures, and improve its service life.
[0016] Preferably, the modified magnolol chain extender is prepared by the following steps: The nano-silicon dioxide is dispersed in anhydrous ethanol, and a nano-silicon dioxide dispersion is obtained after ultrasonic treatment; the silane coupling agent is dispersed in water, the pH is adjusted to acidic, and a hydrolyzed silane coupling agent solution is obtained after stirring; magnolol and the hydrolyzed silane coupling agent solution are added to the nano-silicon dioxide dispersion, heated and stirred for reaction, centrifuged and washed after the reaction is completed, and a modified magnolol chain extender is obtained after drying.
[0017] The modified magnolia phenol chain extender prepared according to the above steps can effectively improve the self-repairing performance, weather resistance, tensile strength and puncture resistance of the invisible car cover.
[0018] Preferably, the raw materials for preparing the self-repairing microcapsules include modified polyamine and urea-formaldehyde resin.
[0019] The self-repairing microcapsules will rupture when the car cover is damaged by scratches or other damages, releasing modified polyamines. The active groups in the modified polyamines can chemically react with other components in the car cover material to form new chemical bonds, repair the damaged areas, and enhance the self-repairing properties of the invisible car cover. Urea-formaldehyde resin has good chemical stability and can resist erosion by external factors such as ultraviolet rays and moisture, protecting the modified polyamines. When damage occurs, the modified polyamines are released to repair scratches, allowing the car cover to maintain good working performance and appearance for a long time, thereby enhancing the service life of the car cover.
[0020] Preferably, the raw materials for preparing the modified polyamine include diethylenetriamine and maleimide.
[0021] Diethylenetriamine contains multiple active amino groups, and maleimide contains carbon-carbon double bonds and imide groups. The modified polyamine formed by the reaction of the two has abundant reactive active sites. When scratches appear on the surface of the car cover and the microcapsules rupture, the modified polyamine is released. Its active sites can react with the active groups in the car cover system to form a new cross-linked structure at the damaged site, thereby realizing the repair function. The modified polyamine can also form connections with surrounding molecules through hydrogen bonds, promote the self-repair of the car cover, and enhance its self-repair performance. The modified polyamine improves the thermal stability and chemical stability by introducing imide groups. The repaired cracks have high strength after release, which can reduce the phenomenon of re-rupture due to external force.
[0022] Preferably, the mass ratio of diethylenetriamine to maleimide is 1:(0.8-1).
[0023] The modified polyamine prepared according to the above mass ratio has good self-healing properties.
[0024] In a second aspect, the present application provides a method for preparing a self-repairing invisible car cover, which adopts the following technical solution: A method for preparing a self-repairing invisible car cover comprises the following steps: Under the protection of neutral gas, polyisocyanate is added to fluorine-containing polyol, and the temperature is raised and stirred while adding, and a prepolymer is obtained after reaction; a composite chain extender is dissolved in a solvent to obtain a chain extender dispersion, and the chain extender dispersion is added to the prepolymer, and the temperature is raised and stirred to react to obtain a polymer; an initiator is dissolved in a solvent to obtain an initiator solution; self-repairing microcapsules are added to the polymer, and after heating and stirring to react, the initiator solution is added, and the reaction is heated and stirred, and the material is discharged after cooling to obtain a self-repairing coating; The adhesive is applied to the surface of a transparent substrate to obtain an adhesive layer, and a release film is covered on the adhesive layer to obtain a semi-finished car cover; the self-repairing coating is applied to the side of the semi-finished car cover away from the release film, and heated and cured to obtain a semi-finished car cover with a self-repairing coating, and a protective film is covered on the self-repairing coating, and after curing, a self-repairing invisible car cover is obtained.
[0025] The self-repairing invisible car cover prepared according to the above steps has good self-repairing performance, weather resistance, tensile resistance and puncture resistance, has a long service life, can resist damage from external stress during use, and maintain good aesthetics.
[0026] In summary, the present application includes at least one of the following beneficial technical effects: 1. Fluorinated polyols reduce surface energy by introducing fluorine atoms, which can improve the weather resistance and chemical corrosion resistance of car covers and prevent stains from adhering. Polyisocyanates react with fluorinated polyols to form a polyurethane network structure, which provides good mechanical strength and stability for the coating and can improve the ability of car covers to resist scratches. Composite chain extenders can effectively adjust the length and structure of polyurethane chains, enhance the flexibility and tensile properties of car covers, and prevent them from breaking when stretched or bent by external forces. Self-healing microcapsules are evenly dispersed in the coating. When scratches or other minor damages appear on the surface of the car cover, the microcapsules break and release repair substances to repair the damaged parts, thereby restoring the integrity and protective function of the car cover. Through the synergistic effect of various components, the self-healing invisible car cover can achieve rapid self-repair after being damaged, effectively reducing damage to the paint during long-term use, and has a long service life and good aesthetics.
[0027] 2. Perfluorohexylpropylene oxide introduces fluorine atoms, giving the material a special molecular structure, which allows the molecular chains to rearrange after being damaged by scratches, prompting the damaged molecular chains to adjust to their original state and enhancing the self-healing performance; the presence of fluorine improves the UV resistance of the car cover, can effectively absorb and scatter ultraviolet rays, and prevent ultraviolet rays from damaging the material molecules. At the same time, the fluorine-containing groups enhance the chemical stability of the material and improve weather resistance; the network structure formed by the polymerization of bio-based polyols and perfluorohexylpropylene oxide has good flexibility and cohesion, and the dense structure formed by fluorine-containing polyols can enhance the overall hardness and toughness of the car cover, improve the tensile and puncture resistance of the car cover, effectively resist damage from external forces, and extend the service life of the car cover.
[0028] 3. Nano-silica modified magnolia phenol, silane coupling agent as a bridge, can effectively introduce uniformly dispersed nano-silica into the coating. Nano-silica can reinforce the defects in the molecular chain, improve its strength, and provide physical space and restrictions for the movement of the molecular chain. When the car cover is damaged, it prompts the car cover to adjust its position more orderly and rearrange to repair scratches; Nano-silica can enhance the car cover's ability to reflect and scatter ultraviolet rays, and reduce the damage of ultraviolet rays to the internal structure of the car cover. Magnolia phenol can enhance the antioxidant properties. The synergistic effect of the two can extend the service life of the car cover and improve its weather resistance; the modified magnolia phenol chain extender introduces nano-silica into the coating molecular chain. The combination of the two enables the car cover to effectively disperse stress, reduce the occurrence of cracks and punctures, and improve its service life. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 It is a cross-sectional view of a self-repairing invisible car cover in an embodiment of the present application.
[0030] Explanation of the accompanying drawings: 1. Protective film; 2. Self-repairing coating; 3. Transparent substrate; 4. Adhesive layer; 5. Release film. DETAILED DESCRIPTION
[0031] The present application discloses a self-repairing invisible car cover and a preparation method thereof. The raw materials used in the present application can be obtained from commercially available raw materials unless otherwise specified. The present application is further described in detail below in conjunction with the embodiments: Raw material description: Bio-based polyol is cashew nut shell oil bio-based polyol, model FX-9001LV, purchased from Guangzhou Haoyi New Materials Technology Co., Ltd., perfluorohexyl propylene oxide (CAS No.: 38565-52-5), tetrabutylammonium bromide (CAS No.: 1643-19-2), nano-silica particle size is 50nm, silane coupling agent model is KH-550 (CAS No.: 919-30-2), magnolol (CAS No.: 528-43-8), diethylenetriamine (CAS No.: 111-40-0), maleimide (CAS No.: 541-59-3), formaldehyde (CAS No.: 5 0-00-0), urea (CAS No.: 57-13-6), sodium dodecylbenzene sulfonate (CAS No.: 25155-30-0), the transparent substrate is made of TPU, the protective film and the release film are made of PET, the adhesive is acrylic adhesive, model 720, purchased from Suzhou Qinchuan Electric Co., Ltd., the polyisocyanate is toluene diisocyanate (CAS No.: 584-84-9), 4,4'-diaminodiphenyl disulfide (CAS No.: 139-65-1), the initiator is azobisisobutyronitrile (CAS No.: 78-67-1), and the solvent is a mixed solvent of toluene and N,N-dimethylformamide with a volume ratio of 1:1.
[0032] Example 1 Preparation of fluorinated polyols The reactor was purged with nitrogen for 30 minutes, 45.45 g of bio-based polyol was added to the reactor, and 4.55 g of perfluorohexylpropylene oxide was added to the reactor under stirring at a speed of 300 rpm. The addition was completed within 2 hours. After the addition was completed, 1 g of tetrabutylammonium bromide was added to the reactor, the temperature was raised to 100°C, and the reaction was stirred and refluxed at a speed of 300 rpm for 6 hours. After cooling to 30°C, impurities were removed by reduced pressure distillation to obtain a product, the product was dissolved in ethyl acetate, solid impurities were removed by filtration, and the filtrate was rotary evaporated to remove the solvent to obtain a fluorine-containing polyol.
[0033] Preparation of modified magnolol chain extender 1.1 g of nano-silica was dispersed in 10 mL of anhydrous ethanol, and a nano-silica dispersion was obtained after ultrasonic treatment; 4.04 g of a silane coupling agent was dispersed in 10 mL of deionized water, and the pH was adjusted to 5 with 1 mol / L hydrochloric acid, and the mixture was stirred at 200 rpm for 1 hour to obtain a hydrolyzed silane coupling agent solution; 4.86 g of magnolol and the hydrolyzed silane coupling agent solution were added to the nano-silica dispersion, and the mixture was stirred at 80° C. and 200 rpm for 1 hour to react. After the reaction was completed, the mixture was centrifuged and washed with deionized water, and dried in an oven at 80° C. to obtain a modified magnolol chain extender.
[0034] Preparation of self-healing microcapsules Pass nitrogen through a four-necked flask for 30 minutes, add 11.11 g of diethylenetriamine into the four-necked flask, and add 8.89 g of maleimide into the four-necked flask under stirring at 200 rpm. The addition is completed within 1 hour. After the addition is completed, heat to 80°C and stir under reflux at 300 rpm for 4 hours. After cooling to room temperature, pour the reaction product into ether, filter and collect the precipitate, wash the precipitate with ether, and dry the washed precipitate at 60°C in vacuo to obtain a modified polyamine.
[0035] The modified polyamine was dissolved in anhydrous ethanol to obtain a modified polyamine solution; a formaldehyde solution with a mass fraction of 37% and urea were mixed in a three-necked flask so that the mass ratio of formaldehyde to urea was 3:4, a 1 mol / L sodium hydroxide solution was used to adjust the pH to 9, and the mixture was stirred at 300 rpm for 1 hour at 80°C to obtain a urea-formaldehyde resin prepolymer solution; the modified polyamine solution was added to the urea-formaldehyde resin prepolymer solution so that the core material ratio was 1:2, and the mixture was stirred at 500 rpm for 20 minutes to obtain a mixed solution, sodium dodecylbenzene sulfonate accounting for 2% of the total mass of the mixed solution was added, and the mixture was emulsified at a speed of 8000 rpm for 10 minutes to obtain an emulsion, the emulsion was adjusted to pH 3 using a 1 mol / L hydrochloric acid aqueous solution, and the mixture was stirred at 200 rpm for 4 hours at 60°C, and after cooling to room temperature, microcapsules were obtained by filtering; the microcapsules were washed with deionized water until neutral, and then dried at 60°C to obtain self-healing microcapsules.
[0036] Making self-repairing invisible car cover Under nitrogen protection, the temperature was raised to 60°C and stirred at a speed of 200 rpm. 15 g of polyisocyanate was added to 20 g of fluorinated polyol. The addition was completed within 1 hour. After the addition was completed, the reaction was continued for 2 hours to obtain a prepolymer; 5 g of a composite chain extender was dissolved in a solvent, and the mass ratio of 4,4'-diaminodiphenyl disulfide and modified magnolia phenol chain extender in the composite chain extender was 1:2 to obtain a chain extender dispersion. The chain extender dispersion was added to the prepolymer, the temperature was raised to 80°C and stirred at a speed of 300 rpm for 2 hours to obtain a polymer; 1 g of an initiator was dissolved in a solvent to obtain an initiator solution, so that the total amount of solvent was 30 g; 10 g of self-healing microcapsules were added to the polymer, stirred at a speed of 200 rpm at 60°C for 30 minutes, the initiator solution was added, and the stirring was continued at a speed of 200 rpm for 1 hour. After cooling, the material was discharged to obtain a self-healing coating.
[0037] The adhesive is applied to the surface of a transparent substrate to obtain an adhesive layer, and a release film is covered on the adhesive layer to obtain a semi-finished car cover; the self-repairing coating is applied to the side of the semi-finished car cover away from the release film, and the semi-finished car cover is heated and cured at 100°C for 2 hours to obtain a semi-finished car cover with a self-repairing coating, and a protective film is covered on the self-repairing coating, and the self-repairing coating is cured in a 50°C curing room for 2 days to obtain a self-repairing invisible car cover.
[0038] Example 2 Preparation of fluorinated polyols The reactor was purged with nitrogen for 30 minutes, 38.46 g of bio-based polyol was added to the reactor, and 11.54 g of perfluorohexylpropylene oxide was added to the reactor under stirring at a speed of 300 rpm. The addition was completed within 2 hours. After the addition was completed, 1 g of tetrabutylammonium bromide was added to the reactor, the temperature was raised to 100°C, and the reaction was stirred and refluxed at a speed of 300 rpm for 6 hours. After cooling to 30°C, impurities were removed by reduced pressure distillation to obtain a product, the product was dissolved in ethyl acetate, solid impurities were removed by filtration, and the filtrate was rotary evaporated to remove the solvent to obtain a fluorine-containing polyol.
[0039] Preparation of modified magnolol chain extender 1.1 g of nano-silica was dispersed in 10 mL of anhydrous ethanol, and a nano-silica dispersion was obtained after ultrasonic treatment; 4.04 g of a silane coupling agent was dispersed in 10 mL of deionized water, and the pH was adjusted to 5 with 1 mol / L hydrochloric acid, and the mixture was stirred at 200 rpm for 1 hour to obtain a hydrolyzed silane coupling agent solution; 4.86 g of magnolol and the hydrolyzed silane coupling agent solution were added to the nano-silica dispersion, and the mixture was stirred at 80° C. and 200 rpm for 1 hour to react. After the reaction was completed, the mixture was centrifuged and washed with deionized water, and dried in an oven at 80° C. to obtain a modified magnolol chain extender.
[0040] Preparation of self-healing microcapsules Pass nitrogen through a four-necked flask for 30 minutes, add 10 g of diethylenetriamine into the four-necked flask, and add 10 g of maleimide into the four-necked flask under stirring at 200 rpm. The addition is completed within 1 hour. After the addition is completed, the temperature is raised to 80°C and stirred at 300 rpm for reflux reaction for 4 hours. After cooling to room temperature, the reaction product is poured into ether, the precipitate is collected by filtration, the precipitate is washed with ether, and the washed precipitate is vacuum dried at 60°C to obtain a modified polyamine.
[0041] The modified polyamine was dissolved in anhydrous ethanol to obtain a modified polyamine solution; a formaldehyde solution with a mass fraction of 37% and urea were mixed in a three-necked flask so that the mass ratio of formaldehyde to urea was 3:4, a 1 mol / L sodium hydroxide solution was used to adjust the pH to 9, and the mixture was stirred at 300 rpm for 1 hour at 80°C to obtain a urea-formaldehyde resin prepolymer solution; the modified polyamine solution was added to the urea-formaldehyde resin prepolymer solution so that the core material ratio was 1:2, and the mixture was stirred at 500 rpm for 20 minutes to obtain a mixed solution, sodium dodecylbenzene sulfonate accounting for 2% of the total mass of the mixed solution was added, and the mixture was emulsified at a speed of 8000 rpm for 10 minutes to obtain an emulsion, the emulsion was adjusted to pH 3 using a 1 mol / L hydrochloric acid aqueous solution, and the mixture was stirred at 200 rpm for 4 hours at 60°C, and after cooling to room temperature, microcapsules were obtained by filtering; the microcapsules were washed with deionized water until neutral, and then dried at 60°C to obtain self-healing microcapsules.
[0042] Making self-repairing invisible car cover Under nitrogen protection, the temperature was raised to 60°C and stirred at a speed of 200 rpm, 30 g of polyisocyanate was added to 40 g of fluorinated polyol, and the addition was completed within 1 hour. After the addition was completed, the reaction was continued for 2 hours to obtain a prepolymer; 10 g of a composite chain extender was dissolved in a solvent, and the mass ratio of 4,4'-diaminodiphenyl disulfide and modified magnolia phenol chain extender in the composite chain extender was 1:2 to obtain a chain extender dispersion, and the chain extender dispersion was added to the prepolymer, and the temperature was raised to 80°C and stirred at a speed of 300 rpm for 2 hours to obtain a polymer; 3 g of an initiator was dissolved in a solvent to obtain an initiator solution, so that the total amount of solvent was 50 g; 20 g of self-healing microcapsules were added to the polymer, and the mixture was stirred at a speed of 200 rpm at 60°C for 30 minutes, the initiator solution was added, and the mixture was continued to be stirred at a speed of 200 rpm for 1 hour, and the material was discharged after cooling to obtain a self-healing coating; The adhesive is applied to the surface of a transparent substrate to obtain an adhesive layer, and a release film is covered on the adhesive layer to obtain a semi-finished car cover; the self-repairing coating is applied to the side of the semi-finished car cover away from the release film, and the semi-finished car cover is heated and cured at 100°C for 2 hours to obtain a semi-finished car cover with a self-repairing coating, and a protective film is covered on the self-repairing coating, and the self-repairing coating is cured in a 50°C curing room for 2 days to obtain a self-repairing invisible car cover.
[0043] Example 3 Preparation of fluorinated polyols The reactor was purged with nitrogen for 30 minutes, 41.67 g of bio-based polyol was added to the reactor, and 8.33 g of perfluorohexylpropylene oxide was added to the reactor under stirring at a speed of 300 rpm. The addition was completed within 2 hours. After the addition was completed, 1 g of tetrabutylammonium bromide was added to the reactor, the temperature was raised to 100°C, and the reaction was stirred and refluxed at a speed of 300 rpm for 6 hours. After cooling to 30°C, impurities were removed by reduced pressure distillation to obtain a product, the product was dissolved in ethyl acetate, solid impurities were removed by filtration, and the filtrate was rotary evaporated to remove the solvent to obtain a fluorine-containing polyol.
[0044] Preparation of modified magnolol chain extender 1.1 g of nano-silica was dispersed in 10 mL of anhydrous ethanol, and a nano-silica dispersion was obtained after ultrasonic treatment; 4.04 g of a silane coupling agent was dispersed in 10 mL of deionized water, and the pH was adjusted to 5 with 1 mol / L hydrochloric acid, and the mixture was stirred at 200 rpm for 1 hour to obtain a hydrolyzed silane coupling agent solution; 4.86 g of magnolol and the hydrolyzed silane coupling agent solution were added to the nano-silica dispersion, and the mixture was stirred at 80° C. and 200 rpm for 1 hour to react. After the reaction was completed, the mixture was centrifuged and washed with deionized water, and dried in an oven at 80° C. to obtain a modified magnolol chain extender.
[0045] Preparation of self-healing microcapsules Pass nitrogen through the four-necked flask for 30 minutes, add 10.53 g of diethylenetriamine into the four-necked flask, and add 9.47 g of maleimide into the four-necked flask under stirring at 200 rpm. The addition is completed within 1 hour. After the addition is completed, the temperature is raised to 80°C and stirred at 300 rpm for reflux reaction for 4 hours. After cooling to room temperature, the reaction product is poured into ether, the precipitate is collected by filtration, the precipitate is washed with ether, and the washed precipitate is vacuum dried at 60°C to obtain a modified polyamine.
[0046] The modified polyamine was dissolved in anhydrous ethanol to obtain a modified polyamine solution; a formaldehyde solution with a mass fraction of 37% and urea were mixed in a three-necked flask so that the mass ratio of formaldehyde to urea was 3:4, a 1 mol / L sodium hydroxide solution was used to adjust the pH to 9, and the mixture was stirred at 300 rpm for 1 hour at 80°C to obtain a urea-formaldehyde resin prepolymer solution; the modified polyamine solution was added to the urea-formaldehyde resin prepolymer solution so that the core material ratio was 1:2, and the mixture was stirred at 500 rpm for 20 minutes to obtain a mixed solution, sodium dodecylbenzene sulfonate accounting for 2% of the total mass of the mixed solution was added, and the mixture was emulsified at a speed of 8000 rpm for 10 minutes to obtain an emulsion, the emulsion was adjusted to pH 3 using a 1 mol / L hydrochloric acid aqueous solution, and the mixture was stirred at 200 rpm for 4 hours at 60°C, and after cooling to room temperature, microcapsules were obtained by filtering; the microcapsules were washed with deionized water until neutral, and then dried at 60°C to obtain self-healing microcapsules.
[0047] Making self-repairing invisible car cover Under nitrogen protection, the temperature was raised to 60°C and stirred at a speed of 200 rpm, 22.5 g of polyisocyanate was added to 30 g of fluorinated polyol, and the addition was completed within 1 hour. After the addition was completed, the reaction was continued for 2 hours to obtain a prepolymer; 7.5 g of a composite chain extender was dissolved in a solvent, and the mass ratio of 4,4'-diaminodiphenyl disulfide and modified magnolol chain extender in the composite chain extender was 1:2 to obtain a chain extender dispersion, and the chain extender dispersion was added to the prepolymer, and the temperature was raised to 80°C and stirred at a speed of 300 rpm for 2 hours to obtain a polymer; 2 g of an initiator was dissolved in a solvent to obtain an initiator solution, so that the total amount of solvent was 40 g; 15 g of self-healing microcapsules were added to the polymer, and the mixture was stirred at a speed of 200 rpm at 60°C for 30 minutes, the initiator solution was added, and the mixture was continued to be stirred at a speed of 200 rpm for 1 hour, and the material was discharged after cooling to obtain a self-healing coating; The adhesive is applied to the surface of a transparent substrate to obtain an adhesive layer, and a release film is covered on the adhesive layer to obtain a semi-finished car cover; the self-repairing coating is applied to the side of the semi-finished car cover away from the release film, and the semi-finished car cover is heated and cured at 100°C for 2 hours to obtain a semi-finished car cover with a self-repairing coating, and a protective film is covered on the self-repairing coating, and the self-repairing coating is cured in a 50°C curing room for 2 days to obtain a self-repairing invisible car cover.
[0048] Example 4 Example 4 is based on Example 3. The only difference between Example 4 and Example 3 is that in Example 4, the amount of bio-based polyol used is 47.62 g, and the amount of perfluorohexylpropylene oxide used is 2.38 g.
[0049] Example 5 Example 5 is based on Example 3. The only difference between Example 5 and Example 3 is that in Example 5, the amount of bio-based polyol used is 35.71 g, and the amount of perfluorohexylpropylene oxide used is 14.29 g.
[0050] Example 6 Example 6 is based on Example 3, and the only difference between Example 6 and Example 3 is that in Example 6, the modified magnolol chain extender is replaced by magnolol.
[0051] Example 7 Example 7 is based on Example 3. The only difference between Example 7 and Example 3 is that in Example 7, the amount of diethylenetriamine used is 12.5 g and the amount of maleimide used is 7.5 g.
[0052] Example 8 Example 8 is based on Example 3. The only difference between Example 8 and Example 3 is that in Example 8, the amount of diethylenetriamine used is 9.09 g, and the amount of maleimide used is 10.91 g.
[0053] Example 9 Example 9 is based on Example 3. The only difference between Example 9 and Example 3 is that in Example 9, the modified polyamine is replaced by diethylenetriamine.
[0054] Comparative Example 1 Comparative Example 1 is based on Example 3, and the only difference between Comparative Example 1 and Example 3 is that in Comparative Example 1, the fluorine-containing polyol is replaced by a bio-based polyol.
[0055] Comparative Example 2 Comparative Example 2 is based on Example 3. The only difference between Comparative Example 2 and Example 3 is that in Comparative Example 2, the composite chain extender is replaced by 4,4'-diaminodiphenyl disulfide.
[0056] Comparative Example 3 Comparative Example 3 is based on Example 3, and the only difference between Comparative Example 3 and Example 3 is that self-healing microcapsules are not added in Comparative Example 3.
[0057] Performance testing (1) Self-healing performance test: At 60°C, a scratch with a depth of 5 μm was made on the sample using a nano scratch tester, and the time required for recovery was recorded. Each sample was tested three times, and the average value was taken after measurement. The results are recorded in Table 1.
[0058] (4) GB1040-79 Plastics Tensile Test Method and GB / T 1865-2009 Paints and Varnishes Artificial Weathering and Artificial Radiation Exposure (Filtered Xenon Arc Radiation) were selected as the standards to test the tensile strength of the specimens before and after aging. Three samples were prepared for each specimen, and the average value was taken after measurement. The test results are recorded in Table 1.
[0059] (2) Weathering test: After peeling off the protective layer and the release layer, the sample was attached to a test steel plate and aged under a UVA-340 ultraviolet lamp for 1000 h. The sample was taken out and observed for fastness grade evaluation. The results are recorded in Table 1.
[0060] (3) Select "GB / T 37841-2019 Test method for puncture resistance of plastic film and sheeting" as the standard, prepare 5 25mm*25mm specimens, select 4 points around the specimen to test the thickness, calculate the average thickness, perform the puncture test at a speed of 100mm / min, calculate the puncture strength, take the average value after measurement, and record the results in Table 1.
[0061] Table 1 Test results of car cover self-repair performance, weather resistance, tensile strength and puncture resistance It can be seen from Table 1 that the self-repairing time of Examples 1-3 is less than 8.56s, the tensile strength is greater than 19.47MPa, the tensile strength after aging is greater than 15.37MPa, and the puncture strength is greater than 75.68N / mm. It can be seen that the self-repairing invisible car cover prepared in the present application has good self-repairing performance, weather resistance, tensile resistance and puncture resistance.
[0062] It can be seen from Table 1 that the only difference between Examples 4-5 and Comparative Example 1 and Example 3 is that the mass ratio of bio-based polyols to perfluorohexylpropylene oxide in Example 4 is 1:0.05, the mass ratio of bio-based polyols to perfluorohexylpropylene oxide in Example 5 is 1:0.4, and Comparative Example 1 replaces the fluorine-containing polyols with bio-based polyols. Compared with Example 3, the performance of Examples 4-5 and Comparative Example 1 is reduced. This is because if the component ratio of the fluorine-containing polyol is destroyed, the introduction of too few fluorine atoms will have limited improvement on the performance, and too many fluorine atoms will affect the stability of the material, resulting in abnormal interactions between components and reducing the performance of the material. If the fluorine element is not introduced, the performance will be further reduced, thereby reducing the self-healing performance, weather resistance, tensile strength and puncture resistance.
[0063] As can be seen from Table 1, the only difference between Example 6, Comparative Example 2 and Example 3 is that in Example 6, the modified magnolia phenol chain extender is replaced by magnolia phenol, and the composite chain extender is replaced by 4,4'-diaminodiphenyl disulfide in Comparative Example 2. Compared with Example 3, the self-repairing performance, weather resistance, tensile strength and puncture resistance of Example 6 and Comparative Example 2 are reduced; this is because the modified magnolia phenol chain extender is replaced by magnolia phenol, lacks the introduction of nano-silica, and the physical reinforcement effect is reduced. At the same time, the antioxidant performance lacks the synergistic enhancement of nano-silica, and the weather resistance is deteriorated, so that the self-repairing performance, weather resistance, tensile strength and puncture resistance are all reduced; if the composite chain extender is replaced by 4,4'-diaminodiphenyl disulfide, it will further affect the synergistic effect between the components, and the performance will be further reduced.
[0064] As can be seen from Table 1, the only difference between Examples 7-9 and Comparative Example 3 and Example 3 is that the mass ratio of diethylenetriamine to maleimide in Example 7 is 1:0.6, the mass ratio of diethylenetriamine to maleimide in Example 8 is 1:1.2, and the modified polyamine is replaced by diethylenetriamine in Example 9. No self-healing microcapsules are added in Comparative Example 3. Compared with Example 3, the self-healing performance, weather resistance, tensile strength and puncture resistance of Examples 7-9 and Comparative Example 3 are all reduced; this is because the component ratio of the modified polyamine is destroyed, and too much or too little maleimide will affect the stability and reactivity of the modified polyamine, thereby affecting the self-healing performance; replacing the modified polyamine with diethylenetriamine, lacking modification treatment, the stability and reactivity of diethylenetriamine will further decrease; and not adding self-healing microcapsules will directly affect the self-healing performance, and the self-healing performance of the material will be greatly reduced.
[0065] This specific embodiment is only an explanation of the present application, and it is not a limitation of the present application. Through the above description, relevant staff can make various changes and modifications without deviating from the technical idea of the present application. The technical scope of the present application is not limited to the content in the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. A self-repairing invisible car cover, characterized in that: It comprises a protective film, a self-repairing coating, a transparent substrate, an adhesive layer and a release film arranged in sequence, wherein the self-repairing coating is obtained by coating a self-repairing coating, and the raw materials for preparing the self-repairing coating include the following components in parts by weight: 20-40 parts of fluorinated polyol Polyisocyanate 15-30 parts 5-10 parts of composite chain extender Self-repairing microcapsules 10-20 parts Initiator 1-3 parts 30-50 parts of solvent.
2. The self-repairing invisible car cover according to claim 1, characterized in that: The raw materials for preparing the fluorine-containing polyol include bio-based polyol and perfluorohexyl propylene oxide.
3. The self-repairing invisible car cover according to claim 2, characterized in that: The mass ratio of the bio-based polyol to perfluorohexyl propylene oxide is 1:(0.1-0.3).
4. The self-repairing invisible car cover according to claim 1, characterized in that: The composite chain extender comprises 4,4'-diaminodiphenyl disulfide and a modified magnolol chain extender.
5. The self-repairing invisible car cover according to claim 4, characterized in that: The raw materials for preparing the modified magnolol chain extender include magnolol body, silane coupling agent and nano silicon dioxide.
6. The self-repairing invisible car cover according to claim 5, characterized in that: The modified magnolol chain extender is prepared by the following steps: The nano-silicon dioxide is dispersed in anhydrous ethanol, and a nano-silicon dioxide dispersion is obtained after ultrasonic treatment; the silane coupling agent is dispersed in water, the pH is adjusted to acidic, and a hydrolyzed silane coupling agent solution is obtained after stirring; magnolol and the hydrolyzed silane coupling agent solution are added to the nano-silicon dioxide dispersion, heated and stirred for reaction, centrifuged and washed after the reaction is completed, and a modified magnolol chain extender is obtained after drying.
7. The self-repairing invisible car cover according to claim 1, characterized in that: The raw materials for preparing the self-repairing microcapsules include modified polyamine and urea-formaldehyde resin.
8. The self-repairing invisible car cover according to claim 7, characterized in that: The raw materials for preparing the modified polyamine include diethylenetriamine and maleimide.
9. The self-repairing invisible car cover according to claim 8, characterized in that: The mass ratio of diethylenetriamine to maleimide is 1:(0.8-1).
10. A method for preparing the self-repairing invisible car cover according to any one of claims 1 to 9, characterized in that: The following steps are involved: Under the protection of neutral gas, polyisocyanate is added to fluorine-containing polyol, and the temperature is raised and stirred while adding, and a prepolymer is obtained after reaction; a composite chain extender is dissolved in a solvent to obtain a chain extender dispersion, and the chain extender dispersion is added to the prepolymer, and the temperature is raised and stirred to react to obtain a polymer; an initiator is dissolved in a solvent to obtain an initiator solution; self-repairing microcapsules are added to the polymer, and after heating and stirring to react, the initiator solution is added, and the reaction is heated and stirred, and the material is discharged after cooling to obtain a self-repairing coating; The adhesive is applied to the surface of a transparent substrate to obtain an adhesive layer, and a release film is covered on the adhesive layer to obtain a semi-finished car cover; the self-repairing coating is applied to the side of the semi-finished car cover away from the release film, and heated and cured to obtain a semi-finished car cover with a self-repairing coating, and a protective film is covered on the self-repairing coating, and after curing, a self-repairing invisible car cover is obtained.
Citation Information
Patent Citations
Self-repaired polyalcohol composite material at room temperature
CN101153108A
Dynamic polymer composition with hybrid structure and application thereof
CN108341963A
Production method of room-temperature self-repairing type waterborne polyurethane car cover with self-extinction effect
CN109517513A
Novel low-free TDI polyurethane curing agent containing fluorocarbon chain and preparation method thereof
CN110963944A
Water-repellent and oil-repellent fluorine polyurethane composition and preparation method thereof
CN112239956A
Cited By
Transparent film for automobile glass and preparation method thereof
CN120519119A
A transparent film for automobile glass and its preparation method
CN120519119B